In fandango (Revista de História Regional, 2007)
This article enphacizes some aspects of the sociability of Fandango, also named, in the 19th Century by the inhabitants of the coast of Paraná, as a function or entertainment. Using judicial criminal documents, we demonstrate moments of repression aimed at that manifestation of popular culture, characterize the participants and reveal the tensions and frontiers inside the entertainment of the period under focus.